2002
DOI: 10.1111/j.1756-1051.2002.tb01621.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollination and reproductive success of two colour variants of a deceptive orchid, Dactylorhiza maculata (Orchidaceae)

Abstract: Polymorphism in petal colour is common in deceptively pollinated plant species. Most of the deceptively pollinated orchids are food frauds, and in most of them, the deception is not mimetic. These plants have conspicuously coloured flowers which they use as the main attractant of naive pollinators. In a field experiment, we studied the response of bumblebees and other types of flower visitors to colour differences between experimentally paired plants of Dactylorhiza maculata, a nectarless food‐deceptive specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…2003). There have been a number of recent studies on polymorphic orchids and the data are mixed with respect to whether pollinators have preferences for rare color morphs, and whether those preferences can maintain floral color variation through negative frequency‐dependent selection (Koivisto et al . 2002; Aragón & Ackerman 2004; Ackerman & Carromero 2005; Tremblay & Ackerman 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2003). There have been a number of recent studies on polymorphic orchids and the data are mixed with respect to whether pollinators have preferences for rare color morphs, and whether those preferences can maintain floral color variation through negative frequency‐dependent selection (Koivisto et al . 2002; Aragón & Ackerman 2004; Ackerman & Carromero 2005; Tremblay & Ackerman 2007).…”
Section: Introductionmentioning
confidence: 99%
“…fluctuating selection), disruptive selection or selection for intermediate or rare color morphs in populations of Clarkia gracilis (Onagraceae; Jones 1996a,b), Dactylorhiza sambucina (Orchidaceae; Gigord et al 2001), Ipomoea purpurea (Convolvulaceae; Rausher & Fry 1993;Subramaniam & Rausher 2000) and Mimulus luteus (Scrophulariaceae; Medel et al 2003). There have been a number of recent studies on polymorphic orchids and the data are mixed with respect to whether pollinators have preferences for rare color morphs, and whether those preferences can maintain floral color variation through negative frequency-dependent selection (Koivisto et al 2002;Aragón & Ackerman 2004;Ackerman & Carromero 2005;Tremblay & Ackerman 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among the wide range of colour variants of orchid flowers, the occurrence of rare hypochromic inflorescences are regularly recorded in natural populations of the common coloured morph (Weiss 1995;Bournérias and Prat 2005;Dormont et al 2010a). In orchids, the behavioural responses of pollinators to white inflorescences in populations of a coloured morph and the possible consequences for plant reproductive success have been poorly investigated (Koivisto et al 2002;Ackerman and Carromero 2005). Dormont et al (2010a) demonstrate for the European species Orchis mascula L. that the presence of white-flowered individuals results in a fourfold increase in the percentage pollination of neighbouring purple-flowered individuals.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that natural levels of color variation might be more influenced by genetic drift than selection. Similarly, Koivisto et al (2002) found no preferences of pollinators for any color variant in Dactylorhiza maculata . It seems that not all of the color polymorphism in flowers affects pollinator activity, and that it might be either linked genetically to other adaptive characters, such as flower size or the number of inflorescences, which also impinge on the reproductive success (Wolfe 1993 ;Galen et al 1987 ;Sobrevila et al 1989) , or to the outcome of phenotypic plasticity (Schemske and Bierzychudek 2001 ;Warren and Mackenzie 2001) .…”
Section: Generalized Food Deceptionmentioning
confidence: 91%
“…A few species exhibit discontinuous, genetically determined variation in flower color resulting in two or several more or less discrete color morphs, such as yellow and purple morphs of Dactylorhiza sambucina or D. romana (Nilsson 1980) . More rarely, petal color is polymorphic, with individuals exhibiting variable-sized spots or nectar guides on darker or lighter backgrounds, as in Dactylorhiza maculata (Koivisto et al 2002) .…”
Section: Generalized Food Deceptionmentioning
confidence: 98%